Are primary care physicians ill equipped to evaluate and treat childhood physical inactivity?. Issue 2 (2nd April 2020) - Stracciolini, Andrea; Luz, Jennifer; Walker, Gregory; Edwards, Nicholas M.; Faigenbaum, Avery D.; Myer, Gregory D.
ABSTRACT: Objective: To investigate primary care physician clinical practice patterns, barriers, and education surrounding pediatric physical activity (PA), and to compare practice patterns by discipline. Study design: Cross-sectional study Methods: 4500 randomly selected pediatricians, family practice, and sports medicine physicians in the United States were surveyed (11% response rate). Main outcome measures were questionnaire answers on clinical effort, attitudes, and barriers surrounding PA, medical education in exercise science, and awareness of ICD-9 diagnostic codes pertaining to physical inactivity. Results: Approximately 15% of patient interaction time was spent on the evaluation and treatment of physical inactivity for a normal weight child. For an overweight or obese child, clinical time spent on PA almost doubles. Regardless of weight, sports medicine physicians spent significantly more time on the evaluation of physical activity compared to family/internal medicine physicians and pediatricians. Mean percentage of time family/internal medicine physicians spent on PA evaluation and treatment was consistently less than sports medicine physicians, and consistently more than pediatricians. Most physicians strongly agreed that PA assessment and treatment are important for disease prevention; only 28% had ever made the diagnosis of childhood physical inactivity. Limited clinical time was identified as a primary barrier to diagnosing childhood physical inactivity. Eighty-five percent of respondents were unaware of ICD-9 codes for reimbursement of PA evaluation. Eighty-one percent reported a paucity of exercise science education in medical school. Conclusion: While physicians report that PA evaluation is important in practice, behavior patterns surrounding time evaluating PA and treating childhood physical inactivity are discrepant. Pediatricians showed less favorable attitudes and effort surrounding PA compared to other primary care disciplines. The majority of physicians are unaware of physical inactivity diagnostic codes, have never made the diagnosis of childhood physical inactivity, and may not be receiving basic pediatric exercise science training required for evaluating and treating childhood physical inactivity.